Effect of frailty on initiation of statins following incident acute coronary syndromes in patients aged ≥75 years. (November 2021) - Lopez, Derrick; Nedkoff, Lee; Briffa, Tom; Preen, David B.; Etherton-Beer, Christopher; Flicker, Leon; Sanfilippo, Frank M
Highlights: Two-thirds of patients were initiated on statins following acute coronary syndrome. Increasing frailty is inversely associated with initiation of statins. Identifying frail people should be the focus of quality improvement interventions. Abstract: Introduction: Statin use for preventing recurrent acute coronary syndromes (ACS) is low in older people due to many clinical factors, including frailty. Using the recently developed hospital frailty risk score, which allows ascertainment of frailty from real-world data, we examined the association between frailty and initiation of statin treatment following incident ACS in patients aged ≥75 years. Our secondary aim was to determine whether non-initiation of statins was associated with more conservative treatment, defined as non-receipt of evidence-based medicines and/or coronary artery procedures. Methods: We used person-linked hospital administrative and Pharmaceutical Benefits Scheme data to identify incident ACS admissions between 2005 and 2008 in Western Australia and prescription medicine use, respectively. Outcomes were receipt of any statin, high-dose statin, beta-blockers, renin-angiotensin system inhibitors (RASI), antiplatelets and coronary artery procedures within six months of the incident ACS and were analysed using multivariable generalised linear regression models. Results: In 1, 558 patients (52.4% female, mean age 82.6 years), initiation of any statin or high-dose statin decreased with increasing frailty. The adjusted risk ratios for any statin were 0.89 (95% CI: 0.82-0.97) and 0.67 (95% CI: 0.54-0.85) for the intermediate- and high-frailty categories compared with the low-frailty category, respectively. Compared with patients who received statins, those not receiving statins were less likely (p<0.001) to receive beta-blockers (80.8% vs 51.5%), RASI (86.9% vs 62.1%), antiplatelets (90.9% vs 65.1%) or a coronary artery procedure (65.9% vs 21.1%). Conclusions: Increasing frailty is inversely associated with initiation of statins and generally leads to a more conservative approach to treatment of older patients with ACS.